Retrospective Analysis of Bone Substitute Material for Traumatic Long Bone Fractures: Sex-Specific Outcomes - Pawelke, Jonas; Vinayahalingam, Vithusha; Heiss, Christian; Khassawna, Thaqif El; Knapp, Gero; Justus Liebig University Giessen (My University, 2023)
Male patients often experience increased bone and muscle loss after traumatic fractures. This study aims to compare the treatment outcomes of male and female patients with large bone defects. A total of 345 trauma patients underwent surgery, with participants divided into two groups: one receiving bone substitute material (BSM) for augmented defects (n = 192) and the other without augmentation (empty defects = ED, n = 153). Outcome parameters were assessed among female (n = 184) and male (n = 161) patients. Descriptive statistics revealed no significant differences between male and female patients. Approximately one-half of the fractures resulted from high-energy trauma (n = 187). The BSM group experienced fewer complications (p = 0.004), including pseudarthrosis (BSM: n = 1, ED: n = 7; p = 0.02). Among female patients over 65, the incidence of pseudarthrosis was lower in the BSM group (p = 0.01), while younger females showed no significant differences (p = 0.4). Radiologically, we observed premature bone healing with subsequent harmonization. Post hoc power analysis demonstrated a power of 0.99. Augmenting bone defects, especially with bone substitute material, may reduce complications, including pseudarthrosis, in female patients. Additionally, this material accelerates bone healing. Further prospective studies are necessary for confirmation.
Keywords: ddc:610